2011
DOI: 10.1159/000330444
|View full text |Cite
|
Sign up to set email alerts
|

Catechin-Rich Grape Seed Extract Supplementation Attenuates Diet-Induced Obesity in C57BL/6J Mice

Abstract: Background: Grape seed extracts (GSE) are known to present health benefits such as antioxidative and anti-obesity effects in animal models. The purpose of this research is to determine whether the specially manufactured GSE, catechin-rich GSE (CGSE), can protect against obesity induced by a high-fat diet (HFD) and to address the mechanism underlying this effect. Methods: The componential analysis of CGSE was performed using liquid chromatography/mass spectrometry. Oxygen consumption and the respiratory quotien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
19
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 53 publications
3
19
1
Order By: Relevance
“…Catechin-rich grape seed extract supplementation upregulated expression of genes related to fatty acid oxidation in mouse livers [8]. We also found that a catechin-rich ChrSd diet downregulated genes related to fatty acid synthesis ( Scd1 , Acot11 , Mogat1 ) while upregulating genes related to fatty acid β-oxidation ( Acsl3 ) compared to a control diet.…”
Section: Discussionmentioning
confidence: 69%
“…Catechin-rich grape seed extract supplementation upregulated expression of genes related to fatty acid oxidation in mouse livers [8]. We also found that a catechin-rich ChrSd diet downregulated genes related to fatty acid synthesis ( Scd1 , Acot11 , Mogat1 ) while upregulating genes related to fatty acid β-oxidation ( Acsl3 ) compared to a control diet.…”
Section: Discussionmentioning
confidence: 69%
“…However, in most of the experiments performed with animals, the body weight-related effects of polyphenols have been observed after the administration of these compounds for a long time and/or at high doses. [41][42][43][44][45] In this study, we show that the administration of GSPE during a short period of time (15 days) and at low doses, comparable to the average human consumption of procyanidins 32,33 when expressed as metabolic dose, significantly reduces the body weight gain and the adiposity of hamsters fed either an STD or an HFD. Our data demonstrate for the first time that GSPE significantly decreases the weight of all of the white adipose depots studied, both visceral and subcutaneous.…”
Section: Discussionmentioning
confidence: 95%
“…In the same respect, research specifically evaluating the beneficial attributes of polyphenols derived from materials such as GSE is also extensive. GSE-derived polyphenols have been shown to combat obesity and T2D by alleviating HF DIO, decreasing blood glucose and insulin resistance, and reducing the expression of obesity biomarkers [89][90][91][92][93] . In contrast, studies of the anti-obesity and anti-diabetic effects of cocoa polyphenols are comparatively few.…”
mentioning
confidence: 99%